Investigating Ethnic Identity Development through Storytelling: Conceptual and Methodological Potential of Narrative Approach - Ignjatović, Natalija; Radosavljević, Jovan; Simić, Nataša (Psihološka istraživanja, 2024)
This review paper critically reassesses the traditional quantitative approach to ethnic identity research and advocates for an alternative narrative methodology. Using Phinney’s status model as a starting point, we propose a shift towards a more comprehensive narrative perspective in investigating ethnic identity development. Survey-based studies, despite its contributions, face limitations in explaining the nuanced developmental process and contextual influences on identity changes, particularly ethnic exploration. Embracing ethnic labels shapes adolescents’ relations with others, their experiences, actions, and available resources, involving the construction of a narrative about the meaning of belonging to a specific group. The narrative approach explores the subjective significance of ethnic experiences, portraying identities as dynamic. It challenges the concept of abrupt transitions, shedding light on the gradual nature and intricacies of ethnic identity changes. Narratives offer a unique lens to understand the content of ethnic identity, revealing attitudes, beliefs, and cultural behaviors which remain unattainable when assessed using rating-scale instruments. We examine the studies which use narratives, describing the methodology applied to the field of ethnic identity development and critically evaluating its implementation. Despite recognizing the transformative potential of narrative practice, the paper acknowledges limitations, including time and resource demands, as well as training requirements and analytical complexity. In conclusion, the paper suggests the exploration of new directions in ethnic identity development research, highlighting the potential benefits of integrating qualitative methods, particularly narratives. This alternative approach could play a significant role in fostering a deeper understanding of ethnic identity in contemporary landscapes.